2019
DOI: 10.1017/s0305000919000539
|View full text |Cite
|
Sign up to set email alerts
|

The bidirectional association between maternal speech and child characteristics

Abstract: Our aim was to assess whether infants influence the quantity and quality of their mothers’ speech to them and, in turn, whether this maternal speech influences children's later language. As 189 mothers interacted with each of their twins at age 0;5, we calculated the number of utterances, the proportion of sensitive utterances, and the proportion of self-repeated utterances they produced. We later assessed the twins’ language comprehension and production when they were 1;6, 2;6, and 5;2. Quantity of maternal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…One study followed a large cohort of twins from infancy, along with their mothers, longitudinally, and found a bidirectional association between maternal speech and child characteristics, including language. Specifically, they demonstrated that infants influenced how their mothers spoke to them, which in turn affected the number of words the children could produce and comprehend later (Mimeau et al, 2019). Comparable results were also found in older children over 2 years old.…”
Section: Intergenerational Effects From Child To Parentmentioning
confidence: 89%
See 2 more Smart Citations
“…One study followed a large cohort of twins from infancy, along with their mothers, longitudinally, and found a bidirectional association between maternal speech and child characteristics, including language. Specifically, they demonstrated that infants influenced how their mothers spoke to them, which in turn affected the number of words the children could produce and comprehend later (Mimeau et al, 2019). Comparable results were also found in older children over 2 years old.…”
Section: Intergenerational Effects From Child To Parentmentioning
confidence: 89%
“…However, this perspective has not yet been applied to matters of adults' academic performance. In contrast, for parental language performance, studies have demonstrated that children's characteristics tend to influence maternal speech (Huttenlocher et al, 2010;Schick et al, 2017;Mimeau et al, 2019). One study followed a large cohort of twins from infancy, along with their mothers, longitudinally, and found a bidirectional association between maternal speech and child characteristics, including language.…”
Section: Intergenerational Effects From Child To Parentmentioning
confidence: 99%
See 1 more Smart Citation
“…A large literature has revealed the extent to which parents adjust and adapt the speech they address to children, although evidence has primarily been collected with mothers (e.g. Mimeau et al, 2020). Prosodic, phonological, morphological, syntactic and other modifications are systematically applied to adult speech (Cychosz et al, 2021;Moscoso del Prado et al, 2020;Roy et al, 2009;Snow, 1995) according to a range of child characteristics, primarily language ability (Dailey & Bergelson, 2023;Pancsofar, 2020) and age (Rowe & Snow, 2020).…”
Section: Parents Adapt Their Child-directed Speechmentioning
confidence: 99%